2016
DOI: 10.1109/tbme.2016.2550045
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Spatiotemporal Ca2+Signal Propagation Along Hepatocyte Cords

Abstract: Objective The purpose of the present study is to model the dynamics of lobular Ca2+ wave propagation induced by an extracellular stimulus and to analyze the effect of spatially systematic variations in cell-intrinsic signaling parameters on sinusoidal Ca2+ response. Methods We developed a computational model of lobular scale Ca2+ signaling that accounts for receptor-mediated initiation of cell-intrinsic Ca2+ signal in hepatocytes and its propagation to neighboring hepatocytes through gap junction-mediated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…We next sought to determine whether a combination of the causal influence network and a dynamic model of hepatocyte Ca 2+ response can yield propagating Ca 2+ waves consistent with experimental observations. We started with a previously-published dynamic model of hepatocyte Ca 2+ response (Verma et al, 2016 ) and extended the model to incorporate cell-cell connectivity suggested by the causal influence network (see Methods). In addition, we modified the model parameters to incorporate zonation patterns of signaling components based on results from recently published single cell RNA-seq study (Halpern et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next sought to determine whether a combination of the causal influence network and a dynamic model of hepatocyte Ca 2+ response can yield propagating Ca 2+ waves consistent with experimental observations. We started with a previously-published dynamic model of hepatocyte Ca 2+ response (Verma et al, 2016 ) and extended the model to incorporate cell-cell connectivity suggested by the causal influence network (see Methods). In addition, we modified the model parameters to incorporate zonation patterns of signaling components based on results from recently published single cell RNA-seq study (Halpern et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…We started with a receptor oriented, ordinary differential equation (ODE)-based model of Ca 2+ signal propagation in a cord of hepatocytes detailed in Verma et al ( 2016 ). Here, we consider the complex spatial features of a liver lobule by allowing the hepatocytes to be connected with more than two other hepatocytes, as was the case in the original model of Verma et al ( 2016 ). In the present computational model, the state of every cell “i” and its interaction with a set of adjacent cells represented by the index “j” is defined by the following system of ODEs:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of mathematical models of hepatic signaling processes were developed, mostly using ordinary differential equations (ODEs). Aspects covered by such models include, e.g., the origin of zonation patterning (e.g., Wnt/β-catenin signaling pathway, Kogan et al, 2012 ; Benary et al, 2013 ), the propagation of calcium waves at the lobular scale involved in the regulation of diverse hepatic functions (Verma et al, 2016 ), or the link between the circadian clock and hepatic metabolism (Woller et al, 2016 ). These models elucidate important features in the regulation and signaling of hepatic function.…”
Section: Computational Liver Models Relevant For Liver Surgeriesmentioning
confidence: 99%